Uncovering the Complexity of Human Personality in the Qur'an: A Theological and Psychological Approach: Menyingkap Kompleksitas Kepribadian Manusia dalam Al-Qur’an: Pendekatan Teologi dan Psikologi (Takwil: Journal of Quran and Hadith Studies, 2025)
The study of human personality as presented in the Qur’an is of notable importance, given its rich intersection between theological concepts and psychological insights in shaping personal character. In today’s world, where moral degradation, increased psychological distress, and spiritual emptiness are increasingly prevalent, there exists a visible dissonance between the ideal human nature (fitrah) and the behavioral patterns observable in modern society. This research seeks to delve into how the Qur’an defines the essential qualities and innate potential of human beings, to identify foundational values that support the development of character, and to analyze their relevance in addressing ethical and psychological concerns in the contemporary context. Employing a qualitative methodology, the study is based on library research and thematic analysis of selected Qur’anic verses that highlight notions of human character, devotion, and leadership. The results reveal that the Qur’an characterizes humans as beings naturally equipped with reason, free will, and a moral compass, capable of fulfilling their dual function as devoted servants of God (‘abd) and responsible stewards of the earth (khalifah). Core Qur’anic values such as perseverance, truthfulness, reliance on God (tawakkul), justice, gratitude, and sincerity are shown to be more than ethical principles—they also support psychological strength and mental stability. The harmony between theological doctrines and psychological wisdom in the Qur’an contributes to a holistic model of human personality, fostering spiritual-mental balance and resilience in facing the complexities of contemporary life.